Implementation of Kurikulum Merdeka and Its Impact on Student Learning Achievement at Madrasah Aliyah Sabilul Hasanah Kabupaten Banyuasin - Ibrahim, Ibrahim; Sari, Putri Novita; Niswah, Choirun (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
This study aims to analyze the implementation of the "Kurikulum Merdeka" (Independent Curriculum) and its impact on student achievement at Madrasah Aliyah Sabilul Hasanah, Banyuasin Regency, South Sumatra Province. The researcher employed a qualitative descriptive approach using qualitative research methods. Data collection methods included observation, interviews, and documentation. The data analysis techniques involved data reduction, data display, data verification, and drawing conclusions. The validity of the data was ensured through source triangulation and technique triangulation. The informants in this study were the school principal, vice principal for curriculum, teachers, and students. Based on the findings and discussion, the implementation process of the Independent Curriculum at Madrasah Aliyah Sabilul Hasanah has been running quite well. This is evidenced by training and mentoring activities for teachers, which motivate them to deliver updated content. The school’s facilities also adequately support learning activities. However, the implementation of the Independent Curriculum did not show a significant impact on student achievement compared to the previous curriculum. Keywords: Independent Curriculum, Student Achievement